1982
DOI: 10.1111/1523-1747.ep12510575
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evidence for Impaired Cellular Immunity in Different Stages of Syphilis

Abstract: Abundant evidence suggests that Treponema pallidum (T.p.) escapes humoral immune defence despite the host produces antibodies early in the infection. Since the serologic responses in syphilis have been studied in detail this paper focuses on the cellular immune mechanisms. For this purpose the leukocyte migration inhibition was investigated in 17 patients in different stages of syphilis. Leukocyte migration inhibition assay was performed before, and 7 days, 3 weeks, 2 mo. and 1 yr after start of treatment. Ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The host's immune system actively participates in the relentless pursuit and elimination of T. pallidum, while T. pallidum skillfully employs various mechanisms to evade immune recognition, such as suppression of host cellular immune responses. 34,35 Macrophages are the frontline cells of innate defence and play a crucial role in the process of T. pallidum infection. A previous study has demonstrated that Tp92, the outer membrane protein of T. pallidum, induces the death of human monocytes in the early stages of T. pallidum infection, which helps T. pallidum to escape recognition and elimination by the host innate immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The host's immune system actively participates in the relentless pursuit and elimination of T. pallidum, while T. pallidum skillfully employs various mechanisms to evade immune recognition, such as suppression of host cellular immune responses. 34,35 Macrophages are the frontline cells of innate defence and play a crucial role in the process of T. pallidum infection. A previous study has demonstrated that Tp92, the outer membrane protein of T. pallidum, induces the death of human monocytes in the early stages of T. pallidum infection, which helps T. pallidum to escape recognition and elimination by the host innate immune system.…”
Section: Discussionmentioning
confidence: 99%
“…During T. pallidum infection, the interplay between the evasion strategies of T. pallidum and the host's innate and adaptive immune responses is a complex and dynamic battle. The host's immune system actively participates in the relentless pursuit and elimination of T. pallidum , while T. pallidum skillfully employs various mechanisms to evade immune recognition, such as suppression of host cellular immune responses 34,35 . Macrophages are the frontline cells of innate defence and play a crucial role in the process of T. pallidum infection.…”
Section: Discussionmentioning
confidence: 99%